The Role of Beliefs for the Sustainability of the Fiscal Constitution - Karl Justus Bernhard Neumärker; Gerald Pech (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 2003)
Why does the government not defect from the constitution? This article focuses on the dynamic restraints the government faces under the rule of law: violations against unconstitutional laws are not punished under the constitution. If a violating government cannot commit itself never to reinstall the constitution enforcing an unconstitutional law becomes difficult. Citizens? expectations to go unpunished when not complying may be self-fulfilling. Deriving the equilibrium of a global game we show that this mechanism is effectively deterring a government from defecting from a constitutionally permissible tax rate.
Keywords: H26; D7; E61; K42; 330; tax evasion; global games; selffulfilling expectations; dynamic policy restraints; Finanzverfassung; Steuerpolitik; Steuerkriminalität; Erwartungstheorie; Spieltheorie; Theorie